Aplikasi teknologi bioflok (BFT) pada kultur ikan nila, Orechromis niloticus) - Ombong, Frandy; Salindeho, Indra R.N (e-Journal BUDIDAYA PERAIRAN, 2016)
This study was aimed to find out the growth rate of Nile Tilapia (Oreochromis niloticus) cultured with biofloc technology, and to understand the dynamic of several water quality parameters during culture period. This experiment was conducted in the Laboratory of Aquaculture Technology, FPIK, UNSRAT.  Several substances were added to stimulate the development of biofloc, which were: 0,3 mL of EM-4 containing probiotic-bacteria Lactobacillus casei dan Saccharomyces cerevisiae.; 15 mL of mollases;  0,5 g of  yeast commonly used to ferment soybean ; 12 g of dolomite.    60 seeds of  nile tilapia,  with an individual weight of 6 g, were stocked in each container.   Fish were fed at a dose of 3% of the total biomass/day at the first week, and the dose was decreased  down to 1% of the total biomass per day afterwards.  Fish were weighed at day-1, day-15 and day-30.   The change of water color and the density of the floc was consistently evaluated using imhoff-cone. The initial weight of the tested individual fish were 6,00 g. After 15 days, the weight was increased to 7,37g, and at the end of the experiment the individual fish weighed 11,47 g. Hence, the absolut growth of the tested fish was 5,47g,  the specific growth rate was 91% and the daily growth rate was 2,11%.    The density of flok reached 9,5 mL/L at the beginning of the second week, which was categorized as very high density.   The density of floc then was decreased to 4 mL/L.   The density of the floc was maintained around 5 mL/L during the experiment. The temperature of the medium was at the range of 26-300C.  The level of ammonia was 0,03mg/L and  the level of  nitrite fluctuated between 0,15-3mg/L, which is normal and safe for biofloc system.  The level of nitrate was 4-55 mg/L, which was quite high for biofloc system but not harmful for fish.   Keywords:  Biofloc, Nile-Tilapia, growth, floc-density